Endovascular therapy for subclavian artery restenosis due to stent strut protrusion with high-resolution angioscopy and three-dimensional optical frequency domain imaging. Issue 6 (December 2018) - Ikeoka, Kuniyasu; Okayama, Keita; Watanabe, Tetsuya; Nanto, Shinsuke; Sakata, Yasushi; Hoshida, Shiro
Abstract: A 47-year-old female patient was admitted with a complaint of severe chest pain on effort. She had a history of effort angina treated using coronary artery bypass with left internal thoracic arterial bypass to the left ascending coronary artery. She also had left subclavian and vertebral arterial stenoses, which were treated with balloon-expandable stents. Exercise stress myocardial perfusion imaging revealed anterior to apex left ventricular myocardial ischemia. Cardiac ischemia due to left subclavian stenosis was diagnosed. We treated the left subclavian arterial stenosis with endovascular therapy. We observed that the vertebral Palmaz stent protruded from the ostium and the jailed subclavian artery on high-resolution angioscopy (Zemporshe with a 0.48-megapixel equivalent resolution; Taisho Biomed Instruments, Osaka, Japan) and optical frequency domain imaging (OFDI). A guide wire was successfully crossed through the Palmaz stent strut, which was confirmed using three-dimensional OFDI. The stent strut was dilated using balloon angioplasty. New imaging technologies are promising tools for improving the efficacy and safety of craniocervical intervention. <Learning objective: New imaging technologies including high-resolution angioscopy and 3D-optical frequency domain imaging have become available for endovascular therapy of peripheral artery disease. They could be used to observe stent strut deformation with high imaging quality and demonstrated successful guidewire passage through the stent strut. High-resolution angioscopic system yields images with higher quality and larger angular field than any other previous angioscopy systems.>